2015
DOI: 10.1177/0194599815621878
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Sinus Malignancies

Abstract: Malignant tumors of the frontal sinus are rare and are more common in males. Squamous cell carcinoma is the most common entity encountered. Of the 4 most common histologies, survival is best for mature B-cell non-Hodgkin's lymphomas and worst for adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Owing to the rarity of SCC arising from the frontal sinus, [ 119 ] principles of reconstruction of frontal bone defects resulting from oncologic ablations are less univocally defined. Cranioplasty through titanium, ceramic, or plastic implants is among the most frequently employed strategies, and most invariably requires a two-stage surgery [ 120 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Owing to the rarity of SCC arising from the frontal sinus, [ 119 ] principles of reconstruction of frontal bone defects resulting from oncologic ablations are less univocally defined. Cranioplasty through titanium, ceramic, or plastic implants is among the most frequently employed strategies, and most invariably requires a two-stage surgery [ 120 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Bhojwani et al. reported that the incidence of frontal sinus malignancies in their study was 0.011 per 100,000 individuals during a 12-year period, with squamous cell carcinoma as the most common histologic etiology, followed by NHL [10] .…”
Section: Discussionmentioning
confidence: 85%
“…Malignancies primarily originating from the frontal sinus (FS) are rarely described in the literature 1–4 . Histologically, squamous cell carcinomas (SCC) make up the majority of malignant paranasal sinus tumours in humans 2–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Malignancies primarily originating from the frontal sinus (FS) are rarely described in the literature 1–4 . Histologically, squamous cell carcinomas (SCC) make up the majority of malignant paranasal sinus tumours in humans 2–5 . Other diagnoses include non‐Hodgkin B‐cell lymphomas, carcinomas‐non‐otherwise‐specified (CA‐NOS) and adenocarcinomas 2–4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation